Two in One! Grafting technique to harvest two spices from a single tree - V A, Muhammed Nissar; S R, Maneesha; T E, Sheeja (Indian Horticulture, 2025)
Malabar tamarind (Garcinia gummi-gutta) and kokum (Garcinia indica) are two underutilized spice crops native to the Western Ghats of India, valued for their culinary uses and health-promoting compound hydroxycitric acid (HCA). Typically grown in home gardens, their cultivation is limited by space constraints and the unproductive nature of male trees. This study explores an innovative interspecific grafting technique enabling both species to be grown on a single tree, thereby enhancing space efficiency and productivity in small-scale gardens. Various grafting approaches nursery grafting, in situ grafting, and top working were evaluated using compatible rootstock-scion combinations, primarily employing Malabar tamarind as the rootstock due to its vigorous growth. Grafting success and canopy architecture were influenced by scion type (orthotropic vs. plagiotropic). The study demonstrates the viability of producing multiple species on a single tree, presenting a sustainable model for high-value spice cultivation in constrained spaces. The approach also offers aesthetic and ecological benefits for home garden ecosystems.